A economia política clássica no Brasil : o pensamento inovador de Eugênio Gudin - Rocha, Neilaine Ramos (2008)
This research is about the innovative thinking of Eugenio Gudin as a Brazilian scholar of the classical political economy. This work focuses his innovative thinking on the economic and political problems of Brazilian society. This dissertation presents the results of a research through five main chapters: In the first chapter we present a literature review of the specialist literature on Gudin, there are shown approaches to Gudin and presented a biographical and bibliographical study of him. The second chapter presents the theoretical assumptions that give identity and intellectual background for this search. The essential theoretical contribution to this work came of Austrian school of economics. In the third chapter, we analyze the economic ideas of Gudin on the various forms of interventionism in the Brazilian economy. The fourth chapter deals with the ideas and policies of Gudin its concept of democracy. In the last chapter we analyze three essential points: 1) the contextualization of Gudin as a scholar of the Classical Political Economy in its version Austrian, 2) its contribution to the economy poIicy in Brazil and, 3) the limitations of the historiographical studies that admits Gudin as an author conservative.